[CrIII8MII6]n+ (MII = Cu, Co) face-centred, metallosupramolecular cubes. Issue 26 (28th April 2016) - O'Connor, H. M.; Sanz, S.; Pitak, M. B.; Coles, S. J.; Nichol, G. S.; Piligkos, S.; Lusby, P. J.; Brechin, E. K.
Abstract : Heterometallic cubes, assembled in a modular fashion from a [CrL3 ] metalloligand and simple M II salts, display interesting encapsulation and magnetic behaviours. Abstract : Four [Cr III 8 M II 6 ] n+ (M II = Cu, Co) coordination cubes of formulae [Cr8 Co6 L24 Cl12 ] (1 ), [Cr8 Co6 L24 (SCN)12 ] (2 ), [Cr8 Cu6 L24 (H2 O)12 ](SO4 )6 (3 ), and [Cr8 Cu6 L24 Cl12 ] (4 ) (where HL is 1-(4-pyridyl)butane-1, 3-dione), were synthesised using the [Cr III L3 ] metalloligand in combination with a variety of M II salts. The metallic skeleton of each cage describes a cube in which the [Cr III L3 ] moieties occupy the eight vertices and the M II ions lie at the centre of the six faces. The axial coordination sites of the M II cations are occupied by either H2 O molecules or Cl − /SCN − anions originating from the M II salt used in the synthesis, resulting in neutral1, 2 and4 and the cage in3 being a 12+ cation; the charge-balancing SO4 2− anions accommodated both inside and outside the cube. Magnetic susceptibility and magnetisation measurements reveal weak exchange between nearest neighbour metal ions, mediated via the L − ligands. The modular assembly of the cubes suggests that any combination of [M III L3 ] metalloligand and M II salt will work, potentially resulting in an enormous family of supramolecular assemblies. The charge of the cubes is controlled by the nature of the ligand occupying the axial sites on the M II ions, suggesting trivial ligand exchange may offer control over, amongst others, solubility, reactivity, post-synthetic modification and substrate specificity. The large internal cavities of the cubes also suggest host–guest chemistry may be a fruiful route to encapsulating magnetic and/or redox active guests which could be employed to control magnetic behaviour, and the construction of multifunctional materials.